2012
DOI: 10.1039/c2cc17101e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of stable adducts of Si(ii) dihydride using a donor–acceptor approach

Abstract: A stable Si(II) dihydride complex, IPr·SiH(2)·BH(3) (IPr = [(HCNDipp)(2)C:]; Dipp = 2,6-(i)Pr(2)C(6)H(3)), was synthesized and preliminary reactivity involving this source of encapsulated silylene is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0
3

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 41 publications
10
99
0
3
Order By: Relevance
“…LSiNPh 2 [15] (1) was prepared as reported in the literature. 1 H, 13 C, and 29 Si NMR spectra were recorded with a Bruker Avance DRX 500 spectrometer, using C 6 D 6 as a solvent. Chemical shifts δ are given relative to SiMe 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LSiNPh 2 [15] (1) was prepared as reported in the literature. 1 H, 13 C, and 29 Si NMR spectra were recorded with a Bruker Avance DRX 500 spectrometer, using C 6 D 6 as a solvent. Chemical shifts δ are given relative to SiMe 4 .…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9] Many important reactivity studies of stable silylenes toward a variety of substrates have been reported. [10][11][12][13][14] Recently we synthesized a functionalized silylene LSiNPh 2 (1) [L = PhC(NtBu) 2 ] by the facile metathesis reaction of LiNPh 2 with LSiCl. [15] Reactions of stable silylenes with organo isothiocyanates are not reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the energies of the frontier orbitals in the EH 2 series (E ¼ Si, Ge, Sn and Pb), SiH 2 is predicted to be both the strongest Lewis base and Lewis acid in the series, and concurrently IPr•SiH 2 •BH 3 (23) is stable in refluxing toluene and only decomposes at ca. 230 C in the solid state under N 2 [66]. For comparison, the previously reported Ge(II) congener IPr•GeH 2 •BH 3 (24) [43] decomposes completely in refluxing toluene to yield IPr•BH 3 and Ge metal (with H 2 evolution).…”
Section: ð6þmentioning
confidence: 97%
“…Later the Rivard group noted that the hydride source Li[AlH 4 ] converted IPr•SiCl 2 •BH 3 (22) into IPr•SiH 2 •BH 3 (23) when short reaction times coupled with an Et 2 O/toluene solvent mixture were employed [66] (Scheme 4); prolonged reaction times led to the formation of copious amounts of the known alane adduct IPr•AlH 3 [67], presumably via a carbene exchange reaction between 23 and the AlH 3 byproduct. Based on the energies of the frontier orbitals in the EH 2 series (E ¼ Si, Ge, Sn and Pb), SiH 2 is predicted to be both the strongest Lewis base and Lewis acid in the series, and concurrently IPr•SiH 2 •BH 3 (23) is stable in refluxing toluene and only decomposes at ca.…”
Section: ð6þmentioning
confidence: 99%
See 1 more Smart Citation